2021
DOI: 10.3390/cancers13112622
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 Gene Mutation Hereditary Diffuse Gastric Cancer Outcomes: Analysis of a Large Cohort, Systematic Review of Endoscopic Surveillance, and Secondary Cancer Risk Postulation

Abstract: Hereditary diffuse gastric cancer (HDGC) is a rare signet-ring cell adenocarcinoma (SRCC) linked to CDH1 (E-cadherin) inactivating germline mutations, and increasingly other gene mutations. Female CDH1 mutation carriers have additional risk of lobular breast cancer. Risk management includes prophylactic total gastrectomy (PTG). The utility of endoscopic surveillance is unclear, as early disease lacks macroscopic lesions. The current systematic biopsy protocols have unknown efficacy, and other secondary cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…Histology-specific enrichment analysis validated prior associations between CDH1 germline variants in LBC and DGC and identified a novel association with CSRCC [ 9 ]. CSRCC is an aggressive adenocarcinoma subtype with a poor prognosis overall and thus determining cancer-risk susceptibility genes presents an unmet need.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Histology-specific enrichment analysis validated prior associations between CDH1 germline variants in LBC and DGC and identified a novel association with CSRCC [ 9 ]. CSRCC is an aggressive adenocarcinoma subtype with a poor prognosis overall and thus determining cancer-risk susceptibility genes presents an unmet need.…”
Section: Discussionmentioning
confidence: 75%
“…In one study, colon cancer was reported in 3 of 238 (1%) CDH1 pathogenic variant carriers, with 1 case of SRCC. Most recently, Benesch et al postulated through clinical observation and data from SEER that SRCC might be enriched among CDH1 variant carriers with signet ring cell gastric cancer [ 9 ]. Notably, there was no increased risk of colon cancer in CDH1 carriers compared to that of the SEER population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic CDH1 mutations in these tumors are also common [ 72 , 73 , 74 , 75 ]. CDH1-associated lobular breast and diffuse gastric cancers are characterized by small, non-cohesive epithelial cells individually dispersed or organized in a single-file linear pattern in a fibrous stroma [ 76 , 77 ]. Although most data support the notion that CDH1 is a tumor suppressor, Kleer and coworkers have shown that in inflammatory breast cancers, E-cadherin seems to exert an opposite role [ 78 ].…”
Section: Cell-to-cell Contacts Adherens Junctions and Emtmentioning
confidence: 99%
“…Gastric SRCCs share no risk factors with conventional intestinal gastric cancers such as Helicobacter pylori infection [ 2 ]. Some gastric SRCCs arise from germline mutations in CDH1 , termed as hereditary diffuse gastric cancers (HDGCs); however, an increasing array of genes are now implicated including CTNNA1 , BRCA2 , S TK11 , SBHB , PRSS1 , ATM , MSR1 , and PALB2 [ 3 , 4 ]. HDGC however comprises only 1–3% of all gastric cancers, leaving the pathogenesis behind most gastric SRCCs unknown and understudied [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…If detected prior to submucosal invasion, prognosis is equivalent or better than that of intestinal gastric adenocarcinomas [ 2 ]. However, the diffuse nature of the disease usually results in detection at advanced stages [ 1 , 4 ]. There remains considerable debate from numerous retrospective epidemiological studies whether SRCC histology is an independent prognostic factor [ 2 ].…”
Section: Introductionmentioning
confidence: 99%